2017
DOI: 10.1186/s12886-017-0400-z
|View full text |Cite
|
Sign up to set email alerts
|

Extensive bilateral corneal edema 6 weeks after cataract surgery: Keratopathy due to Asclepias physocarpa: a case report

Abstract: BackgroundSurgeons may be unaware of the ability of plant toxins to cause corneal damage. Therefore, corneal damage following intraocular surgery due to plant toxins may be misdiagnosed as postoperative infection.Case presentationA 74-year-old man presented with hyperemia and reduced visual acuity in both eyes 6 weeks after uneventful cataract surgery. We observed extensive hyperemia and corneal stromal edema with Descemet’s folds in both eyes.After obtaining a detailed patient history, we diagnosed plant toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 7 publications
3
13
0
Order By: Relevance
“…In this case, cardenolides from the leaf of the Asclepias plant induced corneal edema several hours after the contact to the eye, as in other case reports 1 , 3 . Cardenolides can penetrate the intact cornea without damage to the epithelium, 1 , 2 and cause corneal endothelial toxicity by inhibiting the endothelial Na + /K + -ATPase pump function 1 .…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…In this case, cardenolides from the leaf of the Asclepias plant induced corneal edema several hours after the contact to the eye, as in other case reports 1 , 3 . Cardenolides can penetrate the intact cornea without damage to the epithelium, 1 , 2 and cause corneal endothelial toxicity by inhibiting the endothelial Na + /K + -ATPase pump function 1 .…”
Section: Discussionsupporting
confidence: 63%
“…steroid, may be helpful to alleviate ocular inflammatory symptoms, such as, conjunctival injection 1 . Treatment with topical steroid was often attempted because topical steroid might increase the activity of the remaining Na + /K + -ATPase pump that was not blocked by cardenolides and facilitate the recovery process 1 , 3 , 7 . An experimental study revealed that dexamethasone increased Na + /K + -ATPase pump activity in cultured corneal endothelial cells 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations